Let's calculate the expression step by step:
-
First part: \( 15 \times 10 \times 10 \) \[ 15 \times 10 = 150 \ 150 \times 10 = 1500 \]
-
Second part: \( 5.2 \times 10 \times 10 \times 10 \times 10 \times 10 \)
- This can be simplified as \( 5.2 \times 10^5 \) (since \( 10 \times 10 \times 10 \times 10 \times 10 = 10^5 \)). \[ 5.2 \times 100000 = 520000 \]
-
Now, combine the two parts: \[ 1500 + 520000 = 521500 \]
Thus, the final result of the expression \( 15 \times 10 \times 10 + 5.2 \times 10 \times 10 \times 10 \times 10 \times 10 \) is \( 521500 \).